Prevalence of chlamydia and gonorreheae among transgender women and travestis in five Brazilian capitals, 2019-2021 - Katia Cristina Bassichetto; Sandro Sperandei; Daniel Jason McCartney; Carla Gianna Luppi; Roberto José Carvalho da Silva; Sandra Araújo; Laio Magno; Maria Luíza Bazzo; Gwenda Hughes; Philippe Mayaud; Inês Dourado; Maria Amélia de Sousa Mascena Veras (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To estimate the prevalence and factors associated with the detection of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) in transgender women and travestis in five Brazilian capitals. Methods: Data were obtained from a cross-sectional study conducted between 2019 and 2021, with participants recruited through Respondent Driven Sampling in São Paulo, Campo Grande, Manaus, Porto Alegre and Salvador. Detection of CT and NG was analyzed at three collection sites (anorectal, oropharyngeal and urethral). Mixed logistic regression models were employed to identify associated factors. Results: A total of 1,297 recruited participants provided biological material to detect these infections. The prevalences of CT, NG and coinfection were 11.5%, 13.3% and 3.6%, respectively. Independent associations with CT infections included past (OR=1.73; 95%CI 1.02-2.95), current (OR=2.13; 95%CI 1.23-3.69), and part-time sex work (OR=2.75; 95%CI 1.60-4.75), as well as lifetime injectable drug use (OR=3.54; 95%CI 1.49-8.40). For NG, associations were observed with lifetime injectable drug use (OR=1.91; 95%CI 1.28-2.84) and sexual orientation, including heterosexual (OR=3.44; 95%CI 1.35-8.82), homosexual (OR=5.49; 95%CI 1.89-15.97), and bisexual (OR=3.21; 95%CI 1.06-9.68). Coinfection was associated with use of illicit drugs in the last 12 months (OR=2.34, 95%CI 1.10-5.00), and younger age was associated with all investigated outcomes. Conclusion: Estimated prevalences of CT, NG and co-infection were higher among transgender women and travestis compared to the general population, particularly among younger, individuals engaged in sex work and illicit drug use.